Results of Psychological Training Program To Develop Children and Youth Mainstays for Immune-Strengthening and Surveillance of Family Violence in Children and Youth in Chiang Rai - Jitbantao, Tongrak; Prasunin, Jamaree (Community and Social Development Journal, 2023)
This experimental research aimed to study the result of the psychological training program to develop children and youth mainstays for immune-strengthening and surveillance of family violence in children and youth in Chiang Rai. The sample group was the youth in Chiang Rai aged 15-25 years who had the average score from the questionnaire about the violence in families of children and youth in Chiang Rai from the 75th percentile. The purposive sampling method was used to select 60 samples to participate in the psychological training program by conducting a match pair of children and youth whose averages were similar: 30 youth to the experimental group and 30 youth to the control group. The psychological training program was conducted twice a week, 1.30 to 2 hours each session, five sessions in total within three weeks. The operational step included three stages: Initial, Working, and Ending Stage. Research results demonstrated that the mean of family violence in children and youth in Chiang Rai from the experimental group during the pre-test period was 3.54 and the Standard Deviation (SD) was 0.65, which was high. The mean of family violence and SD during the post-test period was 2.63 and 0.34, which was moderate. The mean of family violence and SD during the post-test period was 2.56 and 0.33, which was moderate. As for children and youth from the control group, the mean of family violence and SD during the pre-test was 3.86, and SD was 0.48, which was high. The mean of family violence, and SD during the post-test period was 3.82 and 0.50, which was high. During the follow-up stage, the mean of family violence and, SD was 3.80 and 3.48, which was high. It proved that the program was successful to some extent due to the increasing mean of family violence.